2009
DOI: 10.1002/eji.200839090
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 and anti‐bacterial immunity: Protection versus tissue damage

Abstract: IL‐17 can impact health in a variety of ways. It is protective for some pathogens but it is also associated with tissue damaging inflammation. By examining the role of IL‐17 in a variety of bacterial infections the mechanisms by which this cytokine mediates both protection and damage can be dissected. A key element in understanding the role of this cytokine is determining where and when it is acting. Dissecting its essential protective role from its immunopathologic role will allow for improved intervention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…In addition, PPARγ deficiency led to an increase in colonic IL-17 expression and Th17 responses. IL-17 is one of the first cytokines released during innate responses and plays an essential role in mucosal defense against extracellular bacteria through neutrophil trafficking [23] which is critical for host defense against various pathogens [24]. Tissue from the whole colon was analyzed for IL-17 gene expression 14 days PI.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PPARγ deficiency led to an increase in colonic IL-17 expression and Th17 responses. IL-17 is one of the first cytokines released during innate responses and plays an essential role in mucosal defense against extracellular bacteria through neutrophil trafficking [23] which is critical for host defense against various pathogens [24]. Tissue from the whole colon was analyzed for IL-17 gene expression 14 days PI.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that IL-17 plays a protective role for the host during bacterial infections (32, 4143). To evaluate if IL-17 affects C. burnetii viability in macrophages, we treated infected macrophages at 24 or 48 hpi with recombinant mouse IL-17A and enumerated viable bacteria 24 hours later using a fluorescent infectious focus-forming unit (FFU) assay in Vero cells (44).…”
Section: Resultsmentioning
confidence: 99%
“…We identified several inflammatory pathways downregulated by C. burnetii T4BSS effector proteins, including IL-17 signaling. Previous studies demonstrated that IL-17 plays a protective role against several pathogens, including L. pneumophila , the closest pathogenic relative to C. burnetii (2527, 41, 42). We found that C. burnetti downregulates the macrophage IL-17 signaling pathway in a T4BSS-dependent manner, protecting the bacteria from IL-17-mediated killing by the macrophage and blocking secretion of pro-inflammatory chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…При этом наблюдаются разнообразные изменения про-филя цитокинов, которые образуют регуляторную сеть и, оказывая плейотропное действие, влияют на пролиферацию и дифференцировку кератиноцитов [1]. T-лимфоциты Th 1 /Th 17 продуцируют при псори-азе в первую очередь медиаторы -интерферон (ИФН-γ), интерлейкины (ИЛ-2, ИЛ-17), фактор некроза опухолей (ФНО-α) [8]. При этом следует отметить и значительную экспрессию цитокинов-регуляторов воспаления (ИЛ-1, ИЛ-6, ИЛ-8), регу-ляторов Т-клеточного иммунного ответа (ИЛ-12, ИЛ-15, ИЛ-18), регуляторов В-клеточного иммун-ного ответа (ИЛ-6, ИЛ-10, ИЛ-16) [7].…”
unclassified